Weavers' Family Organisation and Suicides in Andhra Pradesh and Telangana: A Sociological Analysis. (August 2018) - Rao, N. Sudhakar; Babu, K. Ranjith
A recent revived interest of anthropologists to study the technological impact on the family organisation has indicated that the global economy and technological transformation have led to complex and diversified occupational structures. These have adversely affected the family structure, organisation of certain traditional occupations and social groups, particularly the weavers, so much so that the families have failed to adapt to the changed circumstances. Though this anomic situation has already been explained from the political and economic perspectives, there is a sociological dimension too, which has been neglected largely so far. Hence, this article examines the suicides of weavers in Andhra Pradesh and Telangana states from sociological perspective. This article argues that the struggles of weavers mirror the ongoing changes in a section of Indian society.